Helicopter vibration and risk of reversible myopia among military air crews (Faculty of Medicine Universitas Indonesia, 2002)
We assessed to what extend the risk of reversible myopia of the different degree of helicopter vibrations and other risk factors among military helicopter pilots and flight engineers. The study was a nested case-control design using medical record at the Institute of Aerospace Medicine of the Indonesian Air Force and Medical Directorate of the Indonesian Army (Flying Wing). Cases and controls were military helicopter pilots and flight engineers who had ametropic visual acuity at the time of entry into military service from 1972 until 1992. Reversible myopia means visual acuity corrected of - 0.50 dioptri or less. The final model indicates there was a relationship between vibration level, duration of work and risk of reversible myopia. Helicopter crews exposed to high vibration level had 4.5 times to develop reversible myopia [adjusted odds ratio (OR) = 4.47; 95% confidence intervals (CI) = 1.48 - 13.55] relative to those who exposed to weak vibration level. There was noted a healthy worker's survivor effect. Those who remain work for a longer peiod had less a chance to be myopia. Those who worked for 10 years or more had a lowered risk of 85% to be myopia compared with those who worked for 14 years (adjusted OR = 0.15; 95% CI = 0.03 - 0.87). Helicopter crews exposed to high helicopter vibration had 4.5 times to develop reversible myopia, and a higher risk occurred during the first four years of employment. (Med J Indones 2002; 11: 93-6)Keywords: helicopter vibration, reversible myopia, air crews